Spatial scale in analysis of the dental plaque microbiome. Issue 1 (10th March 2021) - Borisy, Gary G.; Valm, Alex M.
Abstract: Ecologists have long recognized the importance of spatial scale in understanding structure‐function relationships among communities of organisms within their environment. Here, we review historical and contemporary studies of dental plaque community structure in the context of three distinct scales: the micro (1‐10 µm), meso (10‐100 µm) and macroscale (100 µm to ≥1 cm). Within this framework, we analyze the compositional nature of dental plaque at the macroscale, the molecular interactions of microbes at the microscale, and the emergent properties of dental plaque biofilms at the mesoscale. Throughout our analysis of dental plaque across spatial scales, we draw attention to disease and health‐associated structure‐function relationships and include a discussion of host immune involvement in the mesoscale structure of periodontal disease–associated biofilms. We end with a discussion of two filamentous organisms, Fusobacterium nucleatum and Corynebacterium matruchotii, and their relevant contributions in structuring dental plaque biofilms.